Partitioning of hydrophobic organic contaminants between polymer and lipids for two silicones and low density polyethylene. (November 2017) - Smedes, Foppe; Rusina, Tatsiana P.; Beeltje, Henry; Mayer, Philipp
Abstract: Polymers are increasingly used for passive sampling of neutral hydrophobic organic substances (HOC) in environmental media including water, air, soil, sediment and even biological tissue. The equilibrium concentration of HOC in the polymer can be measured and then converted into equilibrium concentrations in other (defined) media, which however requires appropriate polymer to media partition coefficients. We determined thus polymer-lipid partition coefficients ( K PL ) of various PCB, PAH and organochlorine pesticides by equilibration of two silicones and low density polyethylene (LDPE) with fish oil and Triolein at 4 °C and 20 °C. We observed (i) that K PL was largely independent of lipid type and temperature, (ii) that lipid diffusion rates in the polymers were higher compared to predictions based on their molecular volume, (iii) that silicones showed higher lipid diffusion and lower lipid sorption compared to LDPE and (iv) that absorbed lipid behaved like a co-solute and did not affect the partitioning of HOC at least for the smaller molecular size HOC. The obtained K PL can convert measured equilibrium concentrations in passive sampling polymers into equilibrium concentrations in lipid, which then can be used (1) for environmental quality monitoring and assessment, (2) for thermodynamic exposure assessment and (3) for assessing the linkage between passive sampling and the traditionally measured lipid-normalized concentrations in biota. LDPE-lipid partition coefficients may also be of use for a thermodynamically sound risk assessment of HOC contained in microplastics. Graphical abstract: Highlights: Relatively fast lipid diffusion in Silicone and LDPE. Partition coefficients provided for 78 hydrophobic substances. Lipid type and temperature does not affect partitioning. Partitioning not affected by polymer lipid sorption. Passive sampling results can be converted to lipid based equivalent.